Experimental investigations on the effects of asparagine and serine on the polymorphism of calcium carbonate - POLAT, SEVGİ (ELSEVIER, 2020)
The present study investigated the effects of the amino acids asparagine and serine, as additives, on the polymorphic transformation of calcium carbonate (CaCO3) within the concentration range of 25-100 ppm at 30 degrees C and pH 12. The structural composition and morphology of the samples prepared with and without additives were evaluated experimentally through X-ray diffraction (XRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM) analysis. The XRD results showed that the calcite composition of CaCO3 samples prepared with asparagine and serine reduced with increasing concentrations of both additives. SEM images showed that CaCO3 prepared with asparagine and serine had three coexisting crystal forms: cubic-shaped calcite, spherical shaped vaterite, and needle-like aragonite crystals. Moreover, the addition of both additives separately was found to increase the average particle size and Brunauer-Emmett-Teller (BET) specific surface area of the crystals. Higher concentrations of serine and asparagine individually in the crystallization media resulted in a more negative zeta potential. Meanwhile, the thermal behavior, kinetics, and thermodynamics of the CaCO3 crystals were simultaneously evaluated by means of by thermogravimetric analysis (TGA) coupled with Fourier transform infrared (FTIR) and mass spectrometry (MS). The master plots method combined with the Friedman method revealed that the decomposition of CaCO3 prepared in pure media followed the contracting volume mechanism, R-3. Positive values of Delta H and Delta G were obtained for CaCO3 decomposition. (C) 2020 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Calcium carbonate; Polymorphism; Thermal analysis kinetics; Master-plot; TGA/FTIR/MS; DECOMPOSITION KINETICS; THERMAL-DECOMPOSITION; AMINO-ACIDS; CRYSTALLIZATION; MINERALIZATION; PRECIPITATION; TEMPERATURE; CRYSTALS; TRANSFORMATION